109k views
2 votes
49-3m=4m+4 bbbbbbbbbbbbbbbbbbbbbbbb

2 Answers

3 votes

Answer:

m = - 6 . 43

Explanation:

49 - 3m = 4m + 4

= 49 - 4 = 4m + 3m

=45 = 7m

= 6.428571... = m

= m = 6.43

User Endasan
by
5.5k points
2 votes

Answer:

m = 6.43 (approx. )

Explanation:

49 - 3m = 4m + 4

=> 49 - 4 = 4m + 3m

=> 45 = 7m


= > (45)/(7) = m

=> 6.428571... = m

=> m = 6.43 (approx. ) (Ans)

User Fabrice TIERCELIN
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.